Evaporation of the soil water in response to the amount of straw and evaporative demand - Dalmago, Genei Antonio; Bergamaschi, Homero (Agrometeoros, 2018)
This study aimed to evaluate the soil water evaporation in response to the amount of straw on the surface and to the atmospheric evaporative demand. Two experiments were performed in a glass greenhouse at the Federal University of Rio Grande do Sul, in Porto Alegre, Brazil, in 2003. In one experiment, the evaporation was measured with 0, 2, 4, 8 and 16 t ha-1 of oat straw (Avena strigosa) on the soil surface. In another experiment, a fixed covering of 6 t ha-1 of straw was used, and evaporation was measured over five soil drying cycles, displaced in time for promoting different atmospheric demands. A completely randomized design was used in both experiments. Measurements were taken by weighing PVC microlysimeters containing soil monoliths, collected in field areas previously consolidated in no-till and conventional tillage systems. The average evaporation was 24% higher in bare soil than with 16 t ha-1 of straw on the surface. A significant difference was observed among the evaluation cycles, but the evaporation was ever higher in conventional tillage than in no-tilled soil. The vapor pressure deficit of air and the incoming solar radiation were the most important weather variables for the evaporation, regardless of tillage system or straw presence on the soil surface.